Prevalence, associated factors and perinatal outcomes of antepartum depression in Ibadan Nigeria - Ikeola A. Adeoye; Abiodun Sogbesan; Oluyomi Esan (BMC, 2022)
Abstract Background Antepartum depression is the most common mental health disorder in pregnancy and it is also a risk factor for adverse perinatal outcomes. Low and middle income countries like Nigeria bear a higher burden of antepartum depression compared with high income countries. Prioritizing mental health issues among pregnant women is crucial to achieving the Sustainable Development Goals. We determined the prevalence, associated factors and perinatal outcomes of antepartum depression among pregnant women in Ibadan, Nigeria. Methods A prospective cohort study was conducted among 1745 pregnant women enrolled early in pregnancy (≤ 20 weeks) at four comprehensive obstetric facilities within Ibadan metropolis. Antepartum depression was ascertained during the third trimester using the Edinburg Postpartum Depression Scale ≥ 12. The primary exposure was antepartum depression and the outcome variables were the perinatal outcomes. The associated factors assessed included sociodemographic, obstetric, psychological, and lifestyle characteristics. Bi-variate logistic and Poisson regression analyses were used to assess the factors and relative risk for perinatal outcomes of antepartum depression. Results The prevalence of antepartum depression was 14.1%. The significant factors associated with APD after adjusting for confounders were: high income (≥ 20, 000) which was protective (AOR) = 0.59; 95% CI: (0.40 - 0.88); p-value: 0.010] and perceived stress increased the odds of APD in a monotonic fashion: moderate stress [AOR = 2.39; 95% CI: (1.01 - 5.7); p-value: 0.047], high stress [AOR = 6.43; 95% CI: (2.28 - 18.2); p-value: < 0.001]. Preterm delivery was the only significant perinatal outcome [Relative Risk (RR) = 1.66; 95% CI (1.14 - 2.39); p-value =  0.007]. Depression did not increase the risk of having low birth weight babies (p = 0.513), macrosomia (p = 0.894), birth asphyxia (p = 0.317), and caesarean section (p = 0.298). Conclusions APD was prevalent among our study population. The significant factors identified in this study can be targeted to reduce the occurrence of APD among pregnant women in Nigeria through appropriate social and public health interventions which include APD screening, counselling, and the provision of emotional support for pregnant women during antenatal care.